Microstructural characterization of diamond/CBN grains steel braze joint interface using Cu–Sn–Ti active filler alloy. (January 2016) - Liu, S.X.; Xiao, B.; Zhang, Z.Y.; Duan, D.Z.
Abstract: In order to develop the new generation superhard abrasive tools of diamond and cubic boron nitride (CBN), the brazing joint experiments of diamond/CBN crystals and AISI 1045 steel matrix using Cu–Sn–Ti active filler powder alloy were investigated in vacuum furnace. The brazing temperature was 930 °C and the dwelling time was 20 min. Interfacial characteristics of the brazing joint among the diamond/CBN grains, the active filler layer and the steel substrate were analyzed using scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction techniques. The results indicated that Ti element in the Cu–Sn–Ti alloys diffused preferentially to the surface of diamond/CBN grits to form a Ti-rich reaction layer in the brazed joints by microanalyses. Moreover, the TiC, TiN and TiB2 phases in diamond/CBN interface and Cu–Ti phase in steel interface were confirmed by X-ray diffraction phase analysis. The wetting and bonding reactions on diamond/CBN by melting Cu–Sn–Ti alloy were realized through the interfacial reaction products like TiC, TiN and TiB2 compounds during the brazing process. The adhesive strength experiments of the joint interfaces revealed that the grains were not pulled out from the bond interface. The reliable bonding strength of brazed diamond/CBN grains to the steel substrate can meet the application requirements of high efficiency machining in the industrial field. Highlights: A new generation diamond/CBN superhard abrasive brazed tools were proposed. Diamond/CBN grains were brazed onto steel substrate directly using Cu–Sn–Ti powder filler alloys. Interface joining between diamond/CBN and active filler powder was due to the formed Ti–C, Ti–N and Ti–B compound. A reliable joining was achieved between the powder filler and the steel. Interface of steel/alloy exists at cross-diffusion of iron, copper and titanium.